Prehabilitation brings benefits to neurogenesis and peri-operative neurocognitive disorders in amyotrophic rats - Nemoto, Akira; Goyagi, Toru; Sunaga, Satoshi; Nemoto, Wataru; Niiyama, Yukitoshi (European journal of anaesthesiology, 2025)
Peri-operative neurocognitive disorder (PND) is a postoperative complication associated with defects in hippocampal neurogenesis. Pre-operative muscle atrophy is implicated in PND. Although exercise improves cognitive function, its effects on PND remain unclear. This study investigated the relationship between PND and pre-operative exercise (PEx) in adult rats. Animal study. Laboratory. A total of 64 male, 21 weeks old Sprague-Dawley rats were divided into four groups before 2 weeks of tail suspension to induce atopy of the hind legs: nonexercise (NEx) group, NEx with surgery (NEx + S), exercise without surgery (PEx) and pre-operative exercise with surgery (PEx + S). PEx and PEx + S rats were subject to treadmill running for a week before surgery. The rats in the surgery groups were anaesthetised with 3% sevoflurane and underwent abdominal surgery. After a 1 week recovery period following surgery, cognitive function was assessed by a fear conditioning test, and then the Morris water maze test (finding an underwater hidden platform) was conducted over 5 days. Hippocampal neurogenesis was evaluated by assessing brain-derived neurotrophic factor (BDNF) secretion and immunohistochemical labelling. Compared with the NEx rats, there was a retained contextual fear memory ( P  = 0.02), and in the Morris water maze test, the PEx and PEx + S groups found the underwater hidden platform faster ( P  < 0.001) and had a shorter path length ( P  = 0.03). The levels of hippocampal BDNF in the PEx and PEx + S groups were higher than those in the other groups ( P  < 0.001). The number of immature cells in the dentate gyrus was significantly higher in the PEx and PEx + S groups ( P  = 0.004) compared with the NEx and NEx +S groups. In rats, PEx for hind limb muscle atrophy induced by tail suspension reduced PND and increased neurogenesis in the dentate gyrus. We concluded that PEx may reduce PND. Our findings may benefit peri-operative care by improving patient outcomes. Approval number a-1-3012.